Raman spectroscopy studies of the terahertz vibrational modes of a DUT-8 (Ni) metal-organic framework - Krylov, Alexander; Vtyurin, Alexander; Petkov, Petko; Senkovska, Irena; Maliuta, Mariia; Bon, Volodymyr; Heine, Thomas; Kaskel, Stefan; Slyusareva, Evgenia (Physical Chemistry Chemical Physics, 2017)
Low-frequency lattice vibrational modes have been discussed to play a crucial role in the phase transformation process of flexible metal-organic frameworks (MOFs). Therefore, Raman spectroscopy was applied to study the lattice dynamics of a pillared layer DUT-8(Ni) framework (DUT-Dresden University of Technology), existing in rigid and flexible forms. Both the open and the close pore phases could be unambiguously identified by breathing mode bands at 23 cm-1 and 60 cm-1 in the corresponding Raman spectra, showing the efficiency of the technique for monitoring the flexibility of MOF materials as well as the differences in the lattice vibrations of the two phases. Born-Oppenheimer Molecular Dynamics simulations showed that observed low-frequency bands indeed correspond to the oscillation of the breathing mode along the diagonals of the pore channels. Moreover, the directional character of low-frequency vibrations in the flexible version of DUT-8(Ni) could be visualized by the orientation dependent Raman spectroscopy experiment.
CRIS-Team Scopus Importer:2022-04-14